LEGAL PROTECTION ON INDONESIAN LABOR IN ABROAD - Arpangi Arpangi (International Journal of Law Reconstruction, 2018)
The number of cases of migrant workers abroad need to establish protection which is able to overcome the problems or issues that have so far linked with the placement and protection of migrant workers, both before leaving for work and after returning to Indonesia. As stipulated in the Act no. 39 2004 Article 6 that the government is responsible for enhancing the protection of migrant workers abroad, so here takes an active role from the government on how to protect workers without pressure from other parties. In order to protect workers, it is also require the participation of various parties, such as the family of migrant workers, labor organizations, and other parties that exist. In order to provide protection to workers, it is not only the duty of the minister of labor alone, but also the duty of the foreign minister. This is in accordance with the wording of Article 19 (b) of Law No. 37 of 1999 on Foreign Relations, which is representative of the Republic of Indonesia is obliged to provide care, protection and legal aid to citizens and legal entities abroad Indonesia in accordance with national legislation and international law and practice.